2022
DOI: 10.1038/s41416-022-01815-5
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic impact of BET inhibitor BI 894999 treatment: backtranslation from the clinic

Abstract: Background BET inhibitors have been tested in several clinical trials where, despite encouraging preclinical results, substantial clinical benefit in monotherapy remains limited. This work illustrates the translational challenges and reports new data around the novel BET inhibitor, BI 894999. At clinically achievable concentrations, mechanistic studies were carried out to study pathway modulation and rational drug combinations. Methods BRD-NUT fusions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…BET bromodomain inhibitors (iBETs) are successfully employed in the treatment of inflammatory, metabolic, and cardiac disorders, as well as in cancer therapy [ 12 , 112 , 113 , 114 , 115 ]. Since their first identification almost a decade ago, iBETs have attracted considerable interest as anti-tumoral agents, due to their ability to induce an efficient downregulation of c-Myc expression [ 114 , 116 , 117 , 118 ].…”
Section: Bromodomain and Extra-terminal Domain (Bet) Proteinsmentioning
confidence: 99%
“…BET bromodomain inhibitors (iBETs) are successfully employed in the treatment of inflammatory, metabolic, and cardiac disorders, as well as in cancer therapy [ 12 , 112 , 113 , 114 , 115 ]. Since their first identification almost a decade ago, iBETs have attracted considerable interest as anti-tumoral agents, due to their ability to induce an efficient downregulation of c-Myc expression [ 114 , 116 , 117 , 118 ].…”
Section: Bromodomain and Extra-terminal Domain (Bet) Proteinsmentioning
confidence: 99%
“…Bardini et al reported that another BET inhibitor I-BET151 blocked the growth of MLL-AF4+ leukemic cells through affecting the transcription level of BRD4, HOXA7/HOXA9, and RUNX1 [ 150 ]. At present, fourteen BET inhibitors including AZD5153 [ 151 ], BMS-986158 [ 152 ], BI894999 [ 153 ], GS-5829 [ 154 ], GSK525762 [ 155 ], ABBV-075 [ 156 ], CPI-0610 [ 157 ], INCB057643 [ 158 ], OTX-015 [ 159 ], PLX51107 [ 160 ], INCB054329 [ 161 ], FT-1101 [ 162 ], CC-90010 [ 163 ], and ODM-207 [ 164 ] have been entered in the clinical testing.…”
Section: Bet Inhibitorsmentioning
confidence: 99%
“…The catalytic role of BRD proteins in transcription led to the development of small-molecule inhibitors against BRDs. JQ1, the first BRD inhibitor reported [ 172 ], marks a success story of BRD4 as a novel therapeutic vulnerability, and paved the way for several BRD inhibitors with some being under clinical evaluation [ 171 , 173 , 174 , 175 , 176 , 177 , 178 , 179 ]. However, early phase clinical trials show only modest clinical activity as single agents in patients with advanced cancer [ 171 , 179 ].…”
Section: Clinical Advances Of Chemical Degraders In Oncologymentioning
confidence: 99%
“…JQ1, the first BRD inhibitor reported [ 172 ], marks a success story of BRD4 as a novel therapeutic vulnerability, and paved the way for several BRD inhibitors with some being under clinical evaluation [ 171 , 173 , 174 , 175 , 176 , 177 , 178 , 179 ]. However, early phase clinical trials show only modest clinical activity as single agents in patients with advanced cancer [ 171 , 179 ]. This can be explained by the assumption that small molecule BRD inhibitors may only block their chromatin binding function but spare other functional domains [ 171 ].…”
Section: Clinical Advances Of Chemical Degraders In Oncologymentioning
confidence: 99%